PAPP-A enhances the antioxidative effects of IGF-1 during bovine in vitro embryo production - Fagali Franchi, Fernanda; Dos Santos, Priscila Helena [UNESP]; Kubo Fontes, Patricia [UNESP]; Valencise Quaglio, Ana Elisa [UNESP]; Gomes Nunes, Sarah [UNESP]; Zoccal Mingoti, Gisele [UNESP]; de Souza Castilho, Anthony César (Elsevier, 2024)
We investigated whether exogenous pregnancy-associated plasma protein-A (PAPP-A) enhances the antioxidant role of insulin-like growth factor-1 (IGF-1) in bovine in vitro embryo production (IVP). We performed standard in vitro maturation (IVM) and in vitro culture (IVC) or added menadione to promote an oxidative stressed microenvironment and evaluated the antioxidant effect of IGF-1 alone or in combination with PAPP-A (IGF-1/PAPP-A). In IVM, the treatments did not affect oocyte nuclear development, total GSH content, cumulus cell gene expression, and blastocyst yield. Nevertheless, IGF-1/PAPP-A treatment prevented an increase in reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) levels. In IVC, the treatments did not affect the total GSH content on blastocysts and IVC media, but IGF-1 and IGF-1/PAPP-A treatments increased blastocyst yield compared to the menadione group. In addition, IGF-1/PAPP-A treatment had lower ROS levels and regulated genes related to embryonic quality compared to the control and menadione groups. Overall, we showed that PAPP-A could enhance the antioxidant role of IGF-1 during IVP in cattle by avoiding higher ROS levels in oocytes and blastocysts and modulating the transcriptional abundance of genes involved in oxidative protection and embryonic quality.
Keywords: Cattle; Gene expression; Insulin-like growth factor-1; Oxidative stress; Pappalysin; ROS